Manufacturing process of metal composite film

By using in-situ synthesis method in the preparation of metal/ceramic composite films, the problems of prone to cracking and poor mechanical strength of the ceramic film layer are solved, precise control of the film layer thickness and overall performance are achieved, the process is simplified and the process is reduced. cost.

CN119243149APending Publication Date: 2025-01-03NANJING TECH UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411319558.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the preparation process, the existing metal/ceramic composite films have problems such as prone to cracking, peeling and poor mechanical strength of the ceramic film layer, and it is difficult to accurately control the film layer thickness, affecting the overall performance.

Method used

In-situ synthesis method is used to uniformly load the film layer powder on the surface of the porous metal matrix and sinter it in a micro-oxidation atmosphere to generate ceramic phase particles and form a metal/ceramic composite structure, which avoids the difference in thermal expansion coefficient between ceramics and metal materials. Interface stress problems.

Benefits of technology

The film layer thickness is precisely controlled through in-situ synthesis, which enhances the interface bonding strength, significantly improves the overall performance of the composite film, simplifies the process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243149A_ABST
    Figure CN119243149A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing process of a metal composite film. The process comprises the following steps: mixing film layer powder with an additive according to a certain ratio to prepare a suspension, and uniformly loading the suspension on the surface of a porous metal matrix in a proper film coating manner to form a wet film blank; and then, after drying treatment, sintering is carried out in a micro-oxidation atmosphere at 600-1200 DEG C, the film layer powder is synthesized into a ceramic material in situ, and the metal composite film is prepared. According to the preparation method, an in-situ synthesis method is utilized, so that the film layer powder generates ceramic phase particles in the green body, a metal / ceramic composite structure is formed, and the composite film is prepared. Compared with the prior art, the method has the advantages that the problem of interface stress caused by large thermal expansion coefficient difference between ceramic and a metal material is effectively avoided, and the problems that the ceramic film layer in the composite film is easy to crack and peel off and the mechanical strength is poor are successfully solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a manufacturing process of a metal composite membrane, and in particular to an application in preparing a composite membrane by using an in-situ synthesis method on a porous metal substrate to generate ceramic phase particles in a blank to form a metal / ceramic composite structure. Background Art

[0002] Membrane separation technology uses membrane materials as separation media to achieve solid-liquid or gas-solid separation. The driving force on both sides of the membrane (such as pressure difference, concentration difference or potential difference, etc.) is used to selectively pass the components on the raw material side through the membrane, thereby achieving the purpose of separation and purification. Membrane separation technology has the functions of separation, concentration, purification and refinement, and has the advantages of high-efficiency separation, energy saving and environmental protection, simple operation, low investment cost and easy automation control. It is widely used in energy, chemical industry, water treatment, medicine and health, food and environmental protection.

[0003] According to the composition of the material, membranes can be divided into organic membranes and inorganic membranes. Organic membranes have poor stability in acidic and alkaline environments, and usually do not have the performance of high temperature and high pressure resistance, so their application under extreme process conditions is limited. Inorganic membranes mainly include metal membranes and ceramic membranes. Ceramic membranes are often used in high temperature corrosive environments due to their excellent chemical stability and high temperature resistance, but due to the brittleness of ceramic materials, their mechanical strength is low and it is difficult to seal at high temperatures. Although metal membranes have significant advantages in mechanical strength and structural stability, it is difficult to obtain nano-scale metal powders with uniform and stable particle size during the preparation process. In addition, nano-metal particles have high surface energy, are easy to form oxides, and are not corrosion-resistant. Compared with ceramic membranes, it is more difficult to control the pore size of metal membranes, and it is difficult to reduce it to less than 1μm like ceramic membranes.

[0004] Metal / ceramic composite membrane material is a composite separation membrane composed of a porous metal matrix and a ceramic membrane layer. The porous metal matrix is ​​usually made of stainless steel, which has high flux, high strength, high toughness and good welding performance, providing a solid support for the separation layer. The ceramic membrane layer is mainly used to achieve high-precision separation. The metal / ceramic composite membrane combines the advantages of the metal matrix and the ceramic membrane layer, and has many excellent properties: high filtration accuracy, strong acid and alkali resistance, high mechanical strength, good high-temperature sealing, and easy regeneration and cleaning.

[0005] Regarding the preparation of metal / ceramic composite membranes, patent CN100563799C discloses a process for preparing a porous stainless steel-ceramic composite membrane, wherein stainless steel powder and ceramic powder are mixed with additives to obtain a suspension, and a metal powder coating and a ceramic coating are successively prepared on the surface of the substrate. After removing organic matter, they are co-sintered in a vacuum or protective atmosphere to obtain a porous stainless steel-ceramic composite membrane. A layer of metal powder is added between the ceramic layer and the stainless steel substrate, and is co-fired with the ceramic layer at high temperature, which can not only act as an adhesive, but also repair defects on the surface of the substrate without affecting the membrane filtration accuracy. However, this method of introducing a metal transition layer between the substrate and the ceramic layer not only makes the preparation process more complicated, but also increases the cost of membrane preparation. At the same time, how to ensure the high matching between the metal substrate, the transition layer and the ceramic layer is also a challenge. Patent CN111229058B discloses a process for preparing a ceramic composite membrane with a metal protective layer, including a ceramic membrane, a metal powder, a rigid outer mold and a head. The metal powder for preparing the protective layer of the ceramic membrane is placed in a mold consisting of a ceramic membrane, a high-temperature resistant rigid outer mold and a head, and sintered at high temperature under vacuum or a reducing atmosphere. The outer mold is removed to form a ceramic composite membrane material with a metal protective layer. This method can obtain high strength of the metal while ensuring the performance of the ceramic membrane layer. However, this method faces the problems of difficult demolding, easy cracking of the metal membrane layer, and creep of the mold at high temperature and inability to be reused. Patent CN114618316A discloses a porous metal-ceramic composite membrane material and a preparation method thereof, wherein titanium powder is added to stainless steel powder and mixed evenly to obtain a mixed powder; the mixed powder is pressed by cold isostatic pressing, and the obtained porous metal blank is sintered for the first time, and cooled to obtain a porous metal matrix; after the ceramic powder and additives are prepared into a ceramic slurry, the ceramic slurry is formed on the surface of the porous metal matrix to obtain a porous metal-ceramic composite membrane blank; the porous metal-ceramic composite membrane blank is sintered for a second time, and cooled to obtain a porous metal-ceramic composite membrane material. This method aims to reduce the difference in thermal expansion coefficients between the substrate and the ceramic film layer by adding an appropriate amount of active metallic titanium, thereby reducing the risk of cracking or falling off of the film layer during the preparation process. However, this method has several potential problems. First, there may be a risk of uneven mixing of titanium powder and stainless steel powder, which will cause uneven distribution of metallic titanium on the surface of the substrate, thus affecting the overall performance of the film layer. Secondly, metallic titanium has high brittleness, and its addition may reduce the strength of the substrate and affect the mechanical properties of the composite film. Finally, although the purpose of adding metallic titanium is to reduce the difference in thermal expansion coefficients between the substrate and the ceramic film layer, its actual effect may not be as obvious as expected. Summary of the invention

[0006] The present invention provides a manufacturing process for preparing a metal composite film with controllable film thickness by an in-situ synthesis method. The process effectively avoids the interface stress problem caused by the large difference in thermal expansion coefficient between ceramic and metal materials, successfully solves the shortcomings of the prior art, and overcomes the problems of easy cracking and peeling of the ceramic film layer in the composite film and poor mechanical strength.

[0007] The technical solution adopted by the present invention is as follows:

[0008] The membrane powder and additives are mixed in a certain proportion to prepare a suspension, and the suspension is evenly loaded on the surface of the porous metal substrate by a suitable coating method to form a wet membrane body. Then, after drying, sintering is performed at 600-1200°C in a slightly oxidizing atmosphere, and the membrane powder is in-situ synthesized into a ceramic material to obtain a metal composite membrane.

[0009] The manufacturing process of the present invention has the following advantages: 1. The in-situ synthesis method can accurately control the thickness of the film layer during the preparation process; 2. Compared with the existing technology, the in-situ synthesis effectively avoids the interface stress problem caused by the large difference in thermal expansion coefficient between ceramic and metal materials, enhances the interface bonding strength, and significantly improves the overall performance of the composite film; 3. The process is simple and low-cost, and has high potential for industrial application.

[0010] The manufacturing process of the metal composite membrane has the following specific steps: A. Using water or ethanol as solvent, the membrane powder and specific additives are fully mixed in a predetermined ratio to prepare a uniform suspension; B. The suspension is evenly loaded on the surface of the porous metal substrate to form a membrane powder coating; C. The wet film is dried under suitable environmental conditions; D. The dried porous metal blank is placed in a specific sintering environment for sintering. In this process, the membrane powder is used to generate ceramic phase particles in the blank using in-situ synthesis technology, thereby forming a metal / ceramic composite structure; E. After sintering, it is gradually cooled to room temperature to finally obtain a metal composite membrane with excellent performance.

[0011] Preferably, the film layer powder is made of one or more materials selected from zirconium, titanium, nickel, and tungsten, and has an average particle size of 1-50 μm.

[0012] Preferably, the organic matter in the additive contains at least one of a dispersant, a binder or a defoamer.

[0013] Preferably, the dispersant is one or more of polyethylene glycol (PEG), sodium polyacrylate (PAAS), polyethyleneimine (PEI) or polymethacrylic acid.

[0014] Preferably, the binder is one or more of polyvinyl alcohol (PVA), methyl cellulose (MC), carboxymethyl cellulose (CMC) or polyethylene glycol (PEG).

[0015] Preferably, the defoamer is one or more of an organosilicon defoamer, a polyether type, or a silicone ether mixed type.

[0016] Preferably, the suspension uses water or ethanol as solvent; the content of the film layer powder in the suspension is 10-50wt%; the content of the dispersant is 2-6wt%; the content of the binder is 1-5wt%; and the content of the defoamer is 0.1-1wt%.

[0017] Preferably, the coating method is wet powder spraying, dipping, coating or pressing.

[0018] Preferably, the porous metal matrix material may be a green body that has been formed but not sintered, or a matrix that has been sintered once.

[0019] Preferably, the porous metal matrix material is one of austenitic stainless steel powder, ferritic stainless steel powder, titanium or nickel, and has an average particle size of 1-300 μm.

[0020] Preferably, the sintering is carried out in a slightly oxidizing atmosphere, such as O2:Ar, O2:He, CO2:Ar, H2O:N2, etc., with a content of 1:5-1:100, and a sintering temperature of 600-1200° C. By adjusting the concentration of the oxidizing gas, the film powder is slightly oxidized, thereby controlling the thickness of the ceramic layer.

[0021] Preferably, the drying process parameters are: constant temperature of 30-80° C., constant humidity of 25-65% relative humidity, and drying time of 5-24 h.

[0022] Preferably, during the sintering, the temperature is first heated to 300-500°C at a heating rate of 0.2-5°C / min, kept warm for 0.5-3h, then heated to 600-1200°C at a heating rate of 0.5-10°C / min, kept warm for 0.5-5h, and finally cooled to room temperature at a cooling rate of 1-10°C / min.

[0023] The beneficial effects achieved by the present invention are as follows: compared with the prior art, the film thickness is precisely controlled during the preparation process by the in-situ synthesis method. At the same time, the in-situ synthesis technology is used to generate ceramic phase particles in the film powder in the green body to form a metal / ceramic composite structure, thereby preparing a composite film. The interfacial stress problem caused by the large difference in thermal expansion coefficient between ceramic and metal materials is effectively avoided, the interfacial bonding strength is enhanced, and the overall performance of the composite film is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Attached Figure 1 This is a picture of the metal composite film sample of Example 1.

[0025] Attached Figure 2This is a SEM scanning electron microscope image of the metal composite film surface in Example 1.

[0026] Attached Figure 3 This is a SEM scanning electron microscope image of the cross-section of the metal composite film of Example 1. DETAILED DESCRIPTION

[0027] Example 1

[0028] 16g of polyethyleneimine and 0.8g of silicone defoamer were added to 240ml of 4% polyvinyl alcohol solution and stirred to mix evenly. 120g of titanium powder with an average particle size of 1-10μm was slowly added and ultrasonically dispersed for 0.5h to prepare a suspension. A layer of metal powder film was prepared on the surface of a porous stainless steel substrate with an average pore size of 20μm by an impregnation method. After the wet film was dried for 12h at 45℃ and a relative humidity of 40%, it was sintered in a micro-oxygen atmosphere (O2:Ar is 1:15). The sintering process is as follows: first, it was heated to 400℃ at a heating rate of 1℃ / min and kept warm for 2h, then heated to 1050℃ at a heating rate of 2.5℃ / min and kept warm for 3h, and finally cooled to room temperature at a cooling rate of 3℃ / min to obtain a metal composite film with uniform thickness and excellent performance.

[0029] Example 2

[0030] 16g of polyethylene glycol and 0.8g of polyether defoamer were added to 240ml of 4% polyvinyl alcohol solution and stirred to mix evenly. 120g of zirconium powder with an average particle size of 10-20μm was slowly added and ultrasonically dispersed for 0.5h to prepare a suspension. A layer of metal powder film was prepared on the surface of a porous Ti substrate with an average pore size of 30μm by wet powder spraying. After the wet film was dried at 60℃ and 50% relative humidity for 24h, it was sintered in a micro-oxygen atmosphere (O2:He is 1:20). The sintering process is as follows: first, it was heated to 500℃ at a heating rate of 1.5℃ / min and kept warm for 2h, then heated to 1150℃ at a heating rate of 3℃ / min and kept warm for 3h, and finally cooled to room temperature at a cooling rate of 5℃ / min to obtain a metal composite film with uniform thickness and excellent performance.

[0031] Example 3

[0032] 20g of sodium polyacrylate and 1g of silicone defoamer were added to 250ml of 3% methylcellulose solution and stirred to mix evenly. 150g of nickel powder with an average particle size of 30-40μm was slowly added and ultrasonically dispersed for 1h to prepare a suspension. A layer of metal powder film was prepared on the surface of a porous stainless steel substrate with an average pore size of 50μm by coating. After the wet film was dried at 55℃ and relative humidity of 45% for 12h, it was sintered in a micro-oxygen atmosphere (CO2:Ar is 1:20). The sintering process is as follows: first, it was heated to 500℃ at a heating rate of 2℃ / min and kept warm for 2h, then heated to 1000℃ at a heating rate of 3℃ / min and kept warm for 3h, and finally cooled to room temperature at a cooling rate of 4℃ / min to obtain a metal composite film with uniform thickness and excellent performance.

[0033] Example 4

[0034] 15g of polymethacrylic acid and 0.6g of silane mixed defoamer were added to 240ml of 5% polyethylene glycol solution and stirred to mix evenly. 120g of titanium powder with an average particle size of 1-10μm was slowly added and ultrasonically dispersed for 1h to prepare a suspension. A layer of metal powder film was prepared on the surface of a porous Ti substrate with an average pore size of 20μm by an impregnation method. After the wet film was dried for 20h at 60℃ and 50% relative humidity, it was sintered in a micro-oxygen atmosphere (HO2:N2 is 1:30). The sintering process is as follows: first, it was heated to 400℃ at a heating rate of 0.5℃ / min and kept warm for 2h, then heated to 1080℃ at a heating rate of 2℃ / min and kept warm for 3h, and finally cooled to room temperature at a cooling rate of 4℃ / min to obtain a metal composite film with uniform thickness and excellent performance.

[0035] The above embodiments are only used to illustrate the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for manufacturing a metal composite film, the process comprising: The membrane powder is mixed with a dispersant, a binder, and a defoamer in a certain proportion to prepare a suspension, and the suspension is evenly loaded on the surface of a porous metal substrate by a suitable coating method to form a wet membrane body. Then, after drying, it is sintered at 600-1200°C in a slightly oxidizing atmosphere, and the membrane powder is in-situ synthesized into a ceramic material to obtain a metal composite membrane.

2. The process for manufacturing a metal composite film according to claim 1, characterized in that The film layer powder is made of one or more materials selected from zirconium, titanium, nickel and tungsten, and has an average particle size of 1-50 μm.

3. The process for manufacturing the metal composite film according to claim 1, characterized in that The dispersant is one or more of polyethylene glycol (PEG), sodium polyacrylate (PAAS), polyethylene imine (PEI) or polymethacrylic acid; the binder is one or more of polyvinyl alcohol (PVA), methyl cellulose (MC), carboxymethyl cellulose (CMC) or polyethylene glycol (PEG); the defoamer is one or more of silicone defoamer, polyether type or silicone ether mixed type.

4. The process for manufacturing a metal composite film according to claim 1, characterized in that The suspension uses water or ethanol as solvent; the content of metal powder in the suspension is 10-50wt%; the content of dispersant is 2-6wt%; the content of binder is 1-5wt%; and the content of defoamer is 0.1-1wt%.

5. The process for manufacturing the metal composite film according to claim 1, characterized in that The coating method is wet powder spraying, dipping, coating or pressing.

6. The process for manufacturing the metal composite film according to claim 1, characterized in that The porous metal matrix material can be a green body that has been formed but not sintered, or a matrix that has been sintered once.

7. The process for manufacturing a metal composite film according to claim 1, characterized in that The porous metal matrix material is one of austenitic stainless steel powder, ferritic stainless steel powder, titanium or nickel, and its average particle size is 1-300 μm.

8. The process for manufacturing a metal composite film according to claim 1, characterized in that The sintering is carried out in a slightly oxidizing atmosphere, such as O2:Ar, O2:He, CO2:Ar, H2O:N2, etc., with a content of 1:5-1:100, and a sintering temperature of 600-1200°C.

9. The process for manufacturing a metal composite film according to claim 1, characterized in that The drying process parameters are: constant temperature of 30-80°C, constant humidity of 25-65% relative humidity, and drying time of 5-24h.

10. The process for manufacturing a metal composite film according to claim 1, characterized in that During sintering, first heat to 300-500°C at a heating rate of 0.2-5°C / min, keep warm for 0.5-3h, then heat to 600-1200°C at a heating rate of 0.5-10°C / min, keep warm for 0.5-5h, and finally cool to room temperature at a cooling rate of 1-10°C / min.

Citation Information

Patent Citations

  • Preparation technique of porous stainless steel-ceramic compound film

    CN100563799C

  • A process for preparing a ceramic composite film with a metal protective layer

    CN111229058B

  • Porous metal-ceramic composite membrane material and preparation method thereof

    CN114618316A